Visualisation of bacterial behaviour using tapping-mode atomic force microscopy - Gorham, Nicole; Becker, Thomas; Shiers, D.; Watling, Helen (Trans Tech Publications ttp, 2009)
Ex-situ and in-situ Tapping Mode AFM were used to investigate responses of attachedbacteria to stressful conditions. For ex-situ measurements, the AFM was equipped with acustomised re-positioning stage and sample mount to permit re-examination of the same surfacearea. For in-situ measurements, the inoculated pyrite coupon was immersed in solution in a flowthrough cell. Initial experiments using Sulfobacillus thermosulfidooxidans indicated that increasedacidity promoted EPS production but increased salinity resulted in cell detachment.